THE USE OF SPENT RUBBER GRANULES IN THE PRODUCTION OF SCULPTURE WORKS - Muntadhar Sahib Rouah, Mohammed Hamza Al Mamouri, AqeelHussein Al-Anawy, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Tires were recycled and turned into powder. This powder was used in a mixture of polyester resin, cement and some colored oxides in the production of sculpture works after studying its mechanical properties that qualify it for this purpose. The mixture was in proportions (38% of rubber granules) and (47% of polyester resin) and (12% of cement), (2% of hardener) and (1% of colored oxides), where the mixture was examined by means of erosion agents to give the best values ??of shock, hardness, water absorption and mechanical wear. Atmospheric conditions on it to note when irradiating some mixtures, the hardness values ??differ from one mixture to another according to the proportions of the ingredients, and we concluded the use of these mixtures in the production of sculpture works.